The Competency of Teacher Entrepreneurship in Teaching - Natuna, Daeng Ayub; Rinaldi, Rinaldi (International Journal of Economic, Business & Applications, 2017)
Teacher entrepreneurship competence in teaching is a teacher's proficiency to integrate entrepreneurial values when teaching for all subjects, which is measured independently, creative, risk-taking, leadership, action-oriented, and hard work.This study focuses on finding out how high the level of competence of teacher entrepreneurship in teaching, and how big the contribution of each indicator to the variables. The study population was 71 teachers, and the entire population was sampled. Data was collected using questionnaires and was analyzed with descriptive and inferential statistics. The results showed that the competence of teacher entrepreneurship in teaching based on six indicators was obtained with very high interpretation, with value of Mean 4.08 and Standard Deviation 0.83. The contribution of indicator to the variables is classified as lower interpretation (33.36%). The role of teachers in applying the value of entrepreneurship to students must be inderecting on every subject or subject matter when the implementation of learning in the classroom or outdoor. Teachers are expected to have entrepreneurial competence as part of their professional accountability.